Diversity and conservation assessment of orchids in Gunung Ulu Semangko, Selangor, Malaysia - Aqlima, Amiri (2022)
Gunung Ulu Semangko is a part of Selangor State Park (Semangko Forest Reserve). Selangor state park is surrounded by enormous hills and lower mountain forests. The Semangko Forest Reserve (SFR) encompasses The Gap, Gunung Semangko, and Gunung Ulu Semangko, all of which are located in the Titiwangsa range's center part. The SFR is a permanent reserve forest in the Hulu Selangor District of Selangor which is one of the first forest reserves in Selangor that have been gazette on February 11, 1916, with a total size of 1,541 hectares. A diversity study of the orchids has been carried out in Gunung Ulu Semangko and it was the first scientific study specifically on the diversity of orchids. The main aim of this study was to produce a proper scientific documentation on the orchid flora of Gunung Ulu Semangko and their current conservation status. To achieve this aim, fieldwork has been carried out in Gunung Ulu Semangko from January 2020 until November 2021. The species were collected by applying a convivence sampling method and the identification of the species was done based on reliable reference books and websites. Mathematical methods such as Shannon-Weiner Species Diversity Index and Simpson's Diversity Index were used to calculate the diversity of species. For the Evaluation of the conservation status of species, the IUCN Red List guideline was used. Based on this study, a total of 78 species in 30 genera from 2 subfamilies were recorded. From the total collection 85% were epiphytic and 15% were terrestrial orchids. The diversity calculation for Shannon’s index was H= 4.12 and for Simpson’s Index was D=0.98. The high value of H and D was also supported with high values of evenness which was E= 0.96. Five species were found endemic to Peninsular Malaysia and 13 species were endemic to Malesia region. Through observations during the field works road construction, natural disaster, invasive plants, ecotourism and recreational activities, local climate change and human disturbances were threats to the orchids and their habitats in Gunung Ulu Semangko. From the conservation assessment conducted in this study, 27 species were identified as threatened, of which 21 species were fallen in endangered category and six species were fallen under vulnerable category. The rest of orchids were found as not threatened species.